2016
DOI: 10.4049/jimmunol.1500686
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal Expansion of the Lymphatic Vessels Is Regulated by the Sequential Expression of IL-7 and Lymphotoxin α1β2 in Newly Formed Tertiary Lymphoid Structures

Abstract: Lymphangiogenesis associated with tertiary lymphoid structure (TLS) has been reported in numerous studies. However, the kinetics and dynamic changes occurring to the lymphatic vascular network during TLS development have not been studied. Using a viral-induced, resolving model of TLS formation in the salivary glands of adult mice we demonstrate that the expansion of the lymphatic vascular network is tightly regulated. Lymphatic vessel expansion occurs in two distinct phases. The first wave of expansion is depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 46 publications
(51 reference statements)
0
30
0
Order By: Relevance
“…As another cytokine involved in the initiation and maintenance of eLTs within tissues, 29 IL-7 is considered to promote lymphocyte survival by inducing expression of antiapoptotic factor B-cell lymphoma (Bcl) 2 and to regulate early lymphatic vessel expansion. 21 We found that both IL-7 and IL-7 receptor mRNA levels were upregulated similarly in eosinophilic and noneosinophilic NPs with eLTs compared with control tissues and NPs without eLTs (Fig 4, A). Immunofluorescence demonstrated IL-7 expression in eLTs, and scattered IL-7 1 cells were also found in locations other than eLTs (Fig 4, C, HEVs express adhesion molecules, such as intercellular adhesion molecule 1 (ICAM-1) and vascular cell adhesion molecule 1 (VCAM-1), which promote the accumulation of naive lymphocytes from the blood.…”
Section: Upregulated Expression Of Lymphorganogenic Chemokines and Cymentioning
confidence: 74%
See 1 more Smart Citation
“…As another cytokine involved in the initiation and maintenance of eLTs within tissues, 29 IL-7 is considered to promote lymphocyte survival by inducing expression of antiapoptotic factor B-cell lymphoma (Bcl) 2 and to regulate early lymphatic vessel expansion. 21 We found that both IL-7 and IL-7 receptor mRNA levels were upregulated similarly in eosinophilic and noneosinophilic NPs with eLTs compared with control tissues and NPs without eLTs (Fig 4, A). Immunofluorescence demonstrated IL-7 expression in eLTs, and scattered IL-7 1 cells were also found in locations other than eLTs (Fig 4, C, HEVs express adhesion molecules, such as intercellular adhesion molecule 1 (ICAM-1) and vascular cell adhesion molecule 1 (VCAM-1), which promote the accumulation of naive lymphocytes from the blood.…”
Section: Upregulated Expression Of Lymphorganogenic Chemokines and Cymentioning
confidence: 74%
“…Structures of lymphoid aggregates were evaluated by using immunohistochemistry and immunofluorescence, as previously described in prior research. 17,[20][21][22] Antibodies used are listed in Tables E2 and E3 in this article's Online Repository at www.jacionline.org. More information is provided in the Methods section in this article's Online Repository.…”
Section: Immunohistochemistry and Immunofluorescencementioning
confidence: 99%
“…Data obtained from parabiosis experiments and fate mapping experiments by Peduto and colleagues suggest that local, rather than circulating, precursors are responsible for the expansion of the stromal network responsible for TLS establishment (27). Proliferation of the resident stroma has been also observed in an inducible model of TLS, both in the vascular and stromal compartments (134) (Nayar et al, manuscript in preparation), which mimics the expansion of the stromal compartment during immunization in SLOs (22, 180182). Therefore, the most likely scenario is that local differentiation and expansion of tissue-resident mesenchymal cell/s accounts for TLS development.…”
Section: Stromal Fibroblast Organization In Slos and Tlssmentioning
confidence: 92%
“…Only selected circumstances, such as antigen persistence or severity and length of the inflammatory response, may drive the development of lymphoid tissue-like mesenchyme. Part of this complex phenomenon is also reliant on the dramatic changes that both stromal cells and leukocytes induce in the lymphatic and blood vasculature and that occurs as an integral part TLS development (57, 134). In this context, the ability of TLS-associated fibroblasts to secrete pro-angiogenic factors, including VEGF-C and VEGF-D, should also be highlighted (27).…”
Section: Maturation and Stabilization Of Fibroblastic Stromal Cells Amentioning
confidence: 99%
“…90 A possible explanation might be the tight regulation during TLS formation. 129 Although not successful in LTα blocking, probably because of less efficient blockade, blocking LT signalling with an effective LTβR-Ig 130 has been shown to reduce the formation of TLS and inhibit autoimmune disease progression in many different disease models, including T1D, Hashimoto's thyroiditis, and experimental autoimmune encephalomyelitis (EAE). [131][132][133][134] The potent effects of LTβR-Ig in mouse models have pushed a humanized version, Baminercept, into clinical trials.…”
Section: Lymphotoxin Signalling As a Therapeutic Target In Autoimmunementioning
confidence: 99%